From linear to angular isomers : achieving tunable charge transport in single‐crystal indolocarbazoles through delicate synergetic CH/NH⋅⋅⋅π interactions - Jiang, Hui (2020)
Weak intermolecular interaction in organic semiconducting molecular crystals plays an important role in molecular packing and electronic properties. Here, four five‐ring‐fused isomers were rationally designed and synthesized to investigate the isomeric influence of linear and angular shapes in affecting their molecular packing and resultant electronic properties. Single‐crystal field‐effect transistors showed mobility order of 5,7‐ICZ (3.61 cm2 V−1 s−1) >5,11‐ICZ (0.55 cm2 V−1 s−1) >11,12‐ICZ (ca. 10−5 cm2 V−1 s−1) and 5,12‐ICZ (ca. 10−6 cm2 V−1 s−1). Theoretical calculations based on density functional theory (DFT) and polaron transport model revealed that 5,7‐ICZ can reach higher mobilities than the others thanks to relatively higher hole transfer integral that links to stronger intermolecular interaction due to the presence of multiple NH⋅⋅⋅π and CH⋅⋅⋅π(py) interactions with energy close to common NH⋅⋅⋅N hydrogen bonds, as well as overall lower hole‐vibrational coupling owing to the absence of coupling of holes to low frequency modes due to better π conjugation.